Evaluación del régimen impositivo simplificado RISE para contribuyentes del sector norte de la ciudad de Milagro - Valle Plúas, Érika Carolina (2019)
This research work is considered important because of the high rate of informality that exists in Ecuador in terms of merchants who, by not contributing with their taxes, directly affect the General State Budget (PGE), affecting the citizens who stop perceiving the benefits of public services. This research focuses on evaluating the Simplified Ecuadorian Tax Regime (RISE) created as a tax system that facilitates and simplifies the tax payment of a certain sector of taxpayers, besides being a mechanism to reduce informality, increase tax collection , eradicate the evasion of taxes, but above all, create a tax culture in taxpayers. It was taken as a population to the northern sector of the Milagro canton, as it is the sector where most of the merchants are concentrated according to the database obtained from both the Autonomous Decentralized Government (GAD) of the canton and the Internal Revenue Service (SRI)……….